Retomando o fio da meada: uma compreensão sobre a atuação de psicólogos escolares - Azevedo, Liliana Pereira Lima (2014)
We have analyzed, under the theoretical framework of Edgar Morin, how the practice of a school psychologist is exercised at the workplace, since this professional has been suffering criticisms of reductionist actions and must foster, according to the new ideas of the his/her class, the emancipatory ethical and political principles in its educational role as a humanizing practice. The objective of this research was to understand the limits and perspectives which were singled out in the narratives of experience of the professional activity. We have examined how the subjects have faced the daily agitation to conquer their own emancipation and intervene in the educational processes. We have assumed that psychologists are seen as isolated parts of the institutional whole and that is how they often see themselves; they fall short of an educational proposal since they are not emancipated themselves. The methodological approach was oral history, open to listening attentively to the interviewed subjects. Eight subjects participated, all of them with degrees in psychology and working in schools within the state of São Paulo. The results have shown differences in the educational practices of two distinct groups, according to a generational factor. Among them we have noticed that the older group has proved less emancipated, with limitations concerning the perspectives of institutional autonomy and political emancipation. The younger group has shown more involvement and awareness for the development of innovative actions, facing limitations as circumstantial challenges. We have seen that the historical, political and cultural contexts of a given generation, with its respective changes, influence the ways one becomes, thinks and performs. Subjective traits of each one s stories of life, each one complex and singular, are the differential factors that stand out.